Decreases in smoking during treatment for methamphetamine-use disorders: preliminary evidence. Issue 4 (June 2018) - McPherson, Sterling; Orr, Michael; Lederhos, Crystal; McDonell, Michael; Leickly, Emily; Hirchak, Katherine; Oluwoye, Oladunni A.; Murphy, Sean M.; Layton, Matthew; Roll, John M.
Abstract : Despite high rates of smoking (70–90%) and the severely negative impact of smoking on physical and mental health, only 12% of individuals receiving stimulant-use disorder treatment also receive smoking-cessation treatment. The aim of this investigation was to examine the effect of a contingency management (CM) intervention targeting methamphetamine (MA) use on cigarette smoking. Sixty-one adults with MA-use disorders who were smokers were assigned to CM or standard psychosocial treatment. Rates of smoking-negative breath samples (carbon monoxide <3 ppm) were compared between the two groups while controlling for baseline carbon monoxide level, marijuana use, MA use, and time. This subgroup of mostly male (59%) participants included 44 participants in the CM group and 17 participants in the standard psychosocial treatment. Tobacco smoking participants who received CM targeting MA use were 140% (odds ratio: 2.395; 95% confidence interval: 1.073–5.346) more likely to submit a smoking-negative breath sample relative to standard psychosocial treatment during the treatment period, holding constant several other prespecified covariates. This study provides evidence that a behavioral treatment for MA use results in reductions in cigarette smoking in adults with MA-use disorder.